“I saw such islanders” - Lucchetta, Giulio A. (Itinerari, 2023)
The starting point is Shakespeare’s The Tempest as a crucial text of colonialist and postcolonialist literature, which testifies a change from ancient colonies and modern territorial dominions and the developing of different views of Otherness. This drama was a rich mine of metaphors for colonisation, slavery and every effect of decolonisation. For example, it describes the rule of forced education to the colonial language as a way to remove the identity of “savage,” presenting a hard argument developed in the contemporary dramatic reprises of The Tempest, with particular regard to the story of Caliban.